Analisis Dampak Ekonomi, Sosial Budaya dan Lingkungan Pengambilan Material Gunung Turun di Kelurahan Mangunsari Dalam Rangka Pembangunan Waduk Jatibarang - Efa Sulistyani; Kushandajani .; Turtiantoro . (Journal of Politic and Government Studies, 2013)
In implementing a development, the government always involve the community in decision-making that will provide benefits and welfare for the people. Development aimed at achieving better conditions than before. Even so, the government should consider the rules for managing the resources used and the smallest effects arising for the smoothness of a development. Such as Reservoir Development Jatibarang aimed handlers flooding in Semarang which would require the materials to build a dam that is not little. Until eventually determined that the materials used are from Gunung Turun, located in the Village Mangunsari.This study aims to determine the socialization process between the government and the impacts arising from taking Gunung Turun of material in the process of implementation in village communities Mangunsari. The methodology used in this research is descriptive qualitative method, which seeks to describe the state of the real condition of the corresponding data collection was done by in-depth interviews of the informants are considered to know clearly seated problems. It also synthesize several documents that are considered important in this study.From the results obtained are socializing the government in the implementation of development Jatibarang Reservoir is intended to provide the public an overview of the goals and objectives of development and of the impacts that will occur regarding taking the material Gunung Turun. In the process of making the material more or less the same impact as the economic, social and cultural impacts, and environmental impacts that could affect people's lives either directly or indirectly.Keywords: Development, Jatibarang Reservoir, Gunung Turun